2013
DOI: 10.1002/ece3.921
|View full text |Cite
|
Sign up to set email alerts
|

Application ofDNAbarcoding for identification of freshwater carnivorous fish diets: Is number of prey items dependent on size class forMicropterus salmoides?

Abstract: Understanding predator–prey interactions is a major challenge in ecological studies. In particular, the accurate identification of prey is a fundamental requirement in elucidating food-web structure. This study took a molecular approach in determining the species identity of consumed prey items of a freshwater carnivorous fish (largemouth bass, Micropterus salmoides), according to their size class. Thirty randomly selected gut samples were categorized into three size classes, based on the total length of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 41 publications
(82 reference statements)
1
49
0
1
Order By: Relevance
“…A few studies to date have sampled specific aquatic predator taxa more deeply, and demonstrated the occurrence of trophic segregation between different life stages (e.g., age, breeding status, and sex; Alonso et al 2014;Jo et al 2014). Thus, they suggest that different population segments choose different diets.…”
Section: Resolving Substructuring Within Aquatic Species and Populationsmentioning
confidence: 99%
“…A few studies to date have sampled specific aquatic predator taxa more deeply, and demonstrated the occurrence of trophic segregation between different life stages (e.g., age, breeding status, and sex; Alonso et al 2014;Jo et al 2014). Thus, they suggest that different population segments choose different diets.…”
Section: Resolving Substructuring Within Aquatic Species and Populationsmentioning
confidence: 99%
“…None of these methods, however, allow the identification of items that are easily digested or of specific parasitic-host (or predator-prey) interactions, which may cause a bias in data interpretation (Sheppard and Harwood, 2005;Paquin et al, 2014). This may be especially problematic when dealing with small species (Sheppard and Harwood, 2005;Jo et al, 2014;Paquin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In most animal groups, the cytochrome oxidase subunit 1 (COI) is the reference for the DNA barcoding system (Hebert et al, 2003). COI sequences libraries are available through on-line systems (such as GenBank, Bold), enabling its use in the identifications of host or prey species (Valentini et al, 2009;Corse et al, 2010;Leray et al, 2013a;Jo et al, 2014). DNA barcode techniques have been used to determine host-parasitoids webs in arthropods (Hrček and Godfray, 2014), as in Lepidoptera (Janzen et al, 2009) and Hemiptera (Gordon and Weirauch, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…(2014) ensure accurate species identification. The first criterion was acceptance of a species name if the given OTU had ≥98% compliance with a known species.…”
Section: Methodsmentioning
confidence: 99%
“…In freshwater habitats, Jo et al. (2014) showed that DNA‐based approaches permit species level identification and revelation of hidden biodiversity as exemplified by analysis of chironomids in the guts of the generalist predator fish Micropterus salmoides .…”
Section: Introductionmentioning
confidence: 99%